Knowledge and perceptions towards COVID-19 among final year undergraduate medical students and interns in Province 2, Nepal (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Corona Virus Disease-19, the COVID-19, has become a pandemic of public health concern, more so for developing countries like Nepal with an inadequate and vulnerable health system. Among all the seven provinces of the country, Province-2 seems to be at higher risk due to population density and open porous border with neighboring India. This survey was conducted among the undergraduate medical students of medical colleges in Province-2, Nepal to evaluate their knowledge and perception regarding the prevention and spread of the virus.Method: A descriptive cross-sectional study was conducted in September 2020 among final-year undergraduate medical students and interns from Janaki Medical College in Janakpur and National Medical College in Birgunj of Province-2, Nepal. A structured 30-item questionnaire containing demographics (5 items), knowledge (15 items), and perception (10 items) regarding COVID-19 was used for an online survey via email. Ethical approval was taken. Descriptive analysis was performed.Result: A total of 200 out of 250 respondents (>95%) had an adequate level of knowledge on etiology, symptoms, hand hygiene, severity, vulnerability, precautionary measures, and treatment guidelines of COVID-19. More than 80% were ready to work in the hospital during the pandemic with support from their family and nearly half of them (49%) perceived that the preparedness and supplies were sufficient in their institutions.Conclusion: The survey revealed that the majority of the final-year medical students and interns in Province-2 Nepal had adequate knowledge and perception regarding COVID-19.